Sistema de precedentes e a utilização de inteligência artificial como instrumento de acesso à justiça - ARAÚJO, Solânea Silva Dias (2023)
The use of technological tools in the Brazilian justice system has assumed a prominent place, especially artificial intelligence, aiming at reducing the high existing procedural collection in progress, which generates a negative impact in relation to the speed and efficiency of the judicial provision. Thus, considering this scenario of technological change in the legal field, driven by the pandemic period of Covid-19, the theme needs further studies regarding the impacts of the application of these technologies in the execution of legal tasks, as well as their consequences on the fundamental rights set forth in the Federal Constitution of which the following stand out: the reasonable duration of the process and the means that guarantee the celerity of its processing and access to justice. Thus, this research seeks to investigate whether the use of artificial intelligence in the management of the precedents system promotes the right of access to justice, based on the experience with the Athos system of the Superior Court of Justice (STJ), considering the period from 2020 to 2021. Therefore, the inductive method was adopted as an approach method and the monographic, socio-legal-critical and legal-descriptive methods were adopted. As a research technique, the theoretical was used, through a bibliographical review, laws, scientific articles, electronic institutional sites and exploratory field research, accompanied by interviews with STJ servants. In the first chapter, the study began by addressing the evolution of the term access to justice to the present day, establishing an analysis of the relationship between access to justice and the use of technological tools. In the second chapter, the application of artificial intelligence in the management of the precedents system is discussed. In the third chapter, a specific analysis of the Athos system of the STJ continues, observing the contributions of the application of this artificial intelligence in the management of the precedents system, as well as, if the use of this tool promotes or compromises the effectiveness of the right of access to justice. In the final considerations, it is concluded that the use of artificial intelligence in the management of the precedents system provides speed and efficiency in the provision of jurisdiction, without violating constitutional and procedural principles, therefore, it promotes the right of access to justice.